2015
DOI: 10.1016/j.labeco.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Class-size reduction policies and the quality of entering teachers

Abstract: State-wide class-size reduction (CSR) policies have typically failed to produce large achievement gains. One explanation is that the introduction of such policies forces schools to hire relatively low-quality teachers. This paper uses data from an anonymous state to explore whether teacher quality suffered from the introduction of CSR. We find that it did, but not nearly enough to explain the small achievement effects of CSR. The combined fall in achievement due to hiring lower quality teachers and more inexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Moreover, Chetty et al (2014) show that students assigned to high quality teachers have better long-term educational and labour market outcomes. An implication of the above is that the potentially positive effect of smaller classes might be offset by poorer quality teachers (Jepsen & Rivkin 2009, Dieterle 2015.…”
Section: Impact Of Reduced Class Sizementioning
confidence: 99%
“…Moreover, Chetty et al (2014) show that students assigned to high quality teachers have better long-term educational and labour market outcomes. An implication of the above is that the potentially positive effect of smaller classes might be offset by poorer quality teachers (Jepsen & Rivkin 2009, Dieterle 2015.…”
Section: Impact Of Reduced Class Sizementioning
confidence: 99%
“…Prior results for the influence of class size on achievement are mixed. Whereas some studies found that pupils' achievement is reduced in larger classes (Bressoux, 2009;Krueger, 1999), other studies found no effect (Dieterle, 2015;Hoxby, 2000), and still others found that pupils' achievement improves in larger classes (Denny & Oppedisano, 2013). We are able to potentially reconcile these diverse results by applying a specific SFA model that allows for a nonmonotonic influence of class size on academic underachievement (Wang, 2002).…”
mentioning
confidence: 92%